The Franciscans in colonial Mexico - Cohen, Thomas M.; Harrison, Jay T. ca. 20./21. Jh.; Rex Galindo, David; Morales, Francisco (University of Oklahoma Press, 2021)
My Encounter with the Franciscans and with History / Fr. Francisco Morales, OFM -- Visions in the Service of Virtue: Rhetorical Mysticism in Motolinía's Memoriales / Hilaire Kallendorf -- Fray Juan Bautista de Viseo's Missionary Work in Three Languages: A Synthesis of the Sixteenth Century in New Spain / Verónica Murillo Gallegos -- Games, Sacrality, and the Formation of Colonial Society in Mexico City / Jonathan Truitt -- The Landa Conundrum / Matthew Restal -- Sapientia et Doctrina: The Structure of Franciscan Education in San José Province and the Teaching of Alphabetic Literacy among the Yucateca Maya, 1545-1650 / John F. Chuchiak -- The Travels of El devoto peregrino: A Franciscan Holy Land Comes to New Spain / Karen Melvin -- From Celebration to Retreat: Changes in the Discourse on the Martyrdom of Franciscan Missionaries in Central and Northern New Spain, Sixteenth through Nineteenth Centuries / José Refúgio de la Torre Curiel -- The Catholic Missions of the Sierra Gorda before Junípero Serra / Steven W. Hackel -- Congregación and Control: The Franciscan Experience in Baja California / Rose Marie Beebe and Robert Senkewicz -- Defining Time and Space: Franciscans and Bells in Northern New Spain / Kristin Dutcher Mann -- Franciscans in Northeastern New Spain / Cecelia Sheridan Prieto -- Franciscans, Jesuits, and the Desire for Martyrdom in New Spain / Emanuele Colombo.